Why do dairy cows have reproductive problems? How can we solve those reproductive problems? - Britt, J.S. (Kansas Agricultural Experiment Station, 2012)
Except for very low producing herds, management of reproduction does not seem to have much effect on the herd's level of production. To counter this statement, we must ask the question: "If they did not manage reproduction, what would their production level be?" Dairy cows develop reproductive problems from three major categories of causes: man-made, biological, and environmental.
The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy; Reproductive; Management; Records; Treatments